VITALITAS SEBAGAI SALAH SATU INDIKATOR KESEHATAN HUTAN KONSERVASI : Vitality as One of The Conservation Forest Health Indicators - Yullia Indriani; Rahmat Safe’i; Hari Kaskoyo; Arief Darmawan (PERENNIAL, 2020)
Conservation forests have a function that is as a preservation of diversity of plants and animals and their ecosystems. The function of the forest should make the conservation forest must be preserved and the health condition of the forest. The health condition of a conservation forest has a great influence on the surrounding ecosystem. Thus to determine the health condition of the forest, one indicator that can be used is the vitality of the tree. Tree vitality is one indicator that can reflect forest health using tree damage parameters and canopy conditions. This study aims to determine the value of the vitality status of conservation forests that are the KTH SHK Lestari land management area to facilitate management decision making in forest management. The results showed from the making of six Forest Health Monitoring clusters in conservation forests classified as good, moderate and bad, obtained the vitality of the conservation forest for tree damage parameters in the good category (2 clusters), moderate (1 cluster) and bad (3 clusters) whereas for the parameters of the overall canopy conditions the clusters are in the good category (6 clusters). Thus the vitality assessment that has been carried out in the conservation forest of Teluk Pandan District, Pesawaran Regency can be used as one indicator in the health of conservation forests. Keywords: CLI, forest helth monitoring, forest health, VCR, tree vitality.